*THE EFFECT OF CAROUSEL BRAINSTORMING STRATEGY ON THE STUDENTS' READING ACHIEVEMENT AT SMA SARASWATI SERIRIT IN ACADEMIC YEAR 2017/2018 - ., Ni Made Indah Sari; ., Kadek Sonia Piscayanti, S.Pd., M.Pd.; ., G.A.P. Suprianti, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
*Abstract This study was aimed AT investigating whether or not there was a significant difference between the students’ reading achievement taught by using Carousel Brainstorming Strategy and conventional strategy. Post-test only control group design was applied in this study. The population of this study was the eleventh grade students at SMA Saraswati Seririt. The sampling technique used in this study was Cluster Random Sampling. IPS I class and IPS II class were taken as the samples of this study. Through lottery technique, it was determined that IPS I class was assigned as experimental group and IPS II assigned as control group. The experimental group was taught by using Carousel Brainstorming Strategy meanwhile, the control group was taught by using Conventional Strategy (Teacher-Centered). The data was obtained from post-test and was analyzed descriptively and inferentially. The result of post-test showed that the experimental group gained better achievement compare with the control group. It was proven by the mean score of the experimental group which was 83 meanwhile the mean score of the control group was 59. In addition, the result of inferential statistic analysis showed the value of t observed was 15.574 was higher than t critical value (tcv) which was 16.715 at significant level 0.05. From the result, it was found that the null hypothesis (Ho) is rejected. This proved that there was a significant difference in the students’ reading achievement of the eleventh grade students at SMA Saraswati Seririt who were taught by using Carousel Brainstorming Strategy. Kata Kunci : Reading Achievement, Carousel Brainstorming Strategy *Abstract This study was aimed AT investigating whether or not there was a significant difference between the students’ reading achievement taught by using Carousel Brainstorming Strategy and conventional strategy. Post-test only control group design was applied in this study. The population of this study was the eleventh grade students at SMA Saraswati Seririt. The sampling technique used in this study was Cluster Random Sampling. IPS I class and IPS II class were taken as the samples of this study. Through lottery technique, it was determined that IPS I class was assigned as experimental group and IPS II assigned as control group. The experimental group was taught by using Carousel Brainstorming Strategy meanwhile, the control group was taught by using Conventional Strategy (Teacher-Centered). The data was obtained from post-test and was analyzed descriptively and inferentially. The result of post-test showed that the experimental group gained better achievement compare with the control group. It was proven by the mean score of the experimental group which was 83 meanwhile the mean score of the control group was 59. In addition, the result of inferential statistic analysis showed the value of t observed was 15.574 was higher than t critical value (tcv) which was 16.715 at significant level 0.05. From the result, it was found that the null hypothesis (Ho) is rejected. This proved that there was a significant difference in the students’ reading achievement of the eleventh grade students at SMA Saraswati Seririt who were taught by using Carousel Brainstorming Strategy. keyword : *Reading Achievement, Carousel Brainstorming Strategy